Evaluation of a creatinine clearance correction equation based on body fat mass in older Japanese patients with diabetes - Utsumi, Sara; Kondo, Yuki; Harada, Yoshihiko; Yoshida, Akira; Nishimura, Hiroyuki; Narita, Yuki; Irie, Tetsumi; Jinnouchi, Hideaki; Ishitsuka, Yoichi; Hirata, Sumio (Frontiers in Medicine, 2024)
The estimation of creatinine clearance (CCr) in older adult patients with diabetes is subject to deviations from the results of actual measurements because of changes in body composition. In the present study, we aimed to create a correction for the equation used for the estimation of CCr in older adult Asian patients with diabetes using body composition parameters.We enrolled 50 older Japanese patients with diabetes in whom the measured values of CCr were compared with values estimated using the Cockcroft-Gault equation. The relationships between the error in the estimated CCr and body composition parameters were investigated, and the Cockcroft-Gault equation was corrected using the appropriate parameters. To evaluate the generalizability of the corrected equation, the utility of the Cockcroft-Gault equation, which was corrected on the basis of body composition measured using a household body composition meter, was also investigated.Body fat mass (BFM) was closely correlated with the error in the estimated CCr. The BFM-corrected Cockcroft-Gault equation was more accurate than the original equation. Similarly, the error became smaller using BFM measured with a household body composition meter.The BFM-corrected Cockcroft-Gault equation may provide an accurate method of estimating CCr that can be used in general practice..